(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
John Rawls’ Theory of Justice is a great work in political and moral philosophy. It revives the political philosophy from dying and gives liberalism a new shape. His theory is full of justification and argument. The only purpose is to establish just social order. Just social order needs some principles. In deriving these principles Rawls used some concepts –original position and political conception of the person. The aim of these concepts was to make unbiased principles. Original position is a hypothetical situation where everyone is free and equal. That free and equal status will be under veil of ignorance. In this situation, they are to represent each of their particular conception of the good. In Rawls’ Theory of Justice, the political conception of the person is enable them to have the capacity of two moral powers- capacity to take reasonable conception of justice and capacity to choose particular conception of the good. In writing my paper, I have used the descriptive and analytical method. The sole aim of my paper is to show the cause of the Rawls’ usage of these two conception. The cause is to derive unbiased principles of justice. Amartya Sen and others criticise his original position as it does not deal with actual societies and actual condition of the people. Just social order is itself not actual. So, what is not actual that is the present society, to make it ideal we may need the hypothetical situation.